Technology Commercialization DEA and Related Analytical Methods for Evaluating the Use and Implementation of Technical Innovation - Thore, Sten A. (Springer US, 2002)
Technology Commercialization: DEA and Related Analytical Methods for Evaluating The Use and Implementation of Technical Innovation examines both general Research & Development commercialization and targeted new product innovation. New product development is a major occupation of the technical sector of the global economy and is viewed in many ways as a means of economic stability for a business, an industry, and a country. The heart of the book is a detailing of the analytical methods-with special, but not exclusive emphasis on DEA methods-for evaluating and ranking the most promising R & D and technical innovation being developed. The sponsors of the research and development may involve universities, countries, industries, and corporations-all of these sources are covered in the book. In addition, the trade-off of environmental problems vis-à-vis new product development is discussed in a section of the book. Sten Thore (editor and author) has woven together the chapter contributions by a strong group of international researchers into a book that has characteristics of both a monograph and a unified edited volume of well-written papers in DEA, technology evaluation, R&D, and environmental economics. Finally, the use of DEA as an evaluation method for product innovation is an important new development in the field of R&D commercialization
Keywords: Economics, general; Economic Growth; Innovation/Technology Management; Econometrics; Operations Research/Decision Theory; Economics; Management science; Economic growth; Management; Industrial management; Operations research; Decision making; Technische Innovation; Vermarktung; Data Envelopment Analysis; Produktinnovation